Evaluasi Program Kampung Keluarga Berencana (Studi pada Kelompok Sasaran Bina Keluarga Balita di RW X Kelurahan Kampung Bulang Kecamatan Tanjungpinang Timur) - Sri Ambar Rinah; ZAMZAMI A. KARIM; NUR APNI PRAMITA (Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
The Kampung Keluarga Berencana (KB) Program is one of the government's program innovations in strengthening the Family Development Family Planning (KKBPK) Population Program. The focus of this research is Toddler Family Development. The problem that occurs in BKB is that some parents who have done the scales and injections for their babies immediately return home so that the activities of family building for toddlers carried out by BKB and PLKB cadres are not carried out. The purpose of this study was to evaluate the Kampung KB program process in the BKB target group in RW X Kampung Bulang district. The research method used is descriptive with an evaluative approach. The sampling technique used purposive sampling. The informants of this study consisted of the Head of Kampung Bulang, PLKB, BKB cadres and families who have children under five. Data collection techniques are interviews, observation and documentation. The result of this research is that the process of the Kampung KB program in the target group of Bina Keluarga Balita in RW X, Kampung Bulang district, Tanjungpinang Timur Subdistrict, has not fully run well in accordance with the BKB implementation guidelines managed by the Head of BKKBN number 12 of 2018 concerning Integrative Holistic BKB management. The suggestion is that a special time should be provided in the first 1 hour for BKB and in the next 1 hour specifically for posyandu activities, PLKB as a companion in the family development activities of toddlers can reinforce cadres that they are also BKB cadres, training and coaching for all BKB and need to be socialized back to families who have toddlers regarding toddler family building.